Call for regulation of social media health content: an initiative of the Italian Association of Hospital Dermatologists (ADOI) - Fortunato Cassalia; Andrea Danese; Carmine D'Acunto; Antonio Russo; Corrado Zengarini; Ignazio Stanganelli; Francesco Cusano; Fabrizio Fantini; Salvatore Amato; Davide Melandri; Cesare Massone; Anna Belloni Fortina (Dermatology Reports)
Social media platforms have become integral to healthcare communication, particularly in dermatology, where visual assessment and patient education are paramount. While platforms like Instagram, Facebook, and Twitter offer significant opportunities to raise awareness about skin health, promote preventive measures, and encourage early detection of dermatological conditions, the unregulated dissemination of health information poses substantial risks due to misinformation. In response to these challenges, the Italian Association of Hospital Dermatologists (ADOI) has launched a nationwide survey titled "Use of Social Media by Dermatology Professionals: Impact on Public Awareness, Appropriateness of Information, and Correctness of Prevention Messages—An Italian Survey".